Determinación de los factores de riesgo de aborto en adolescentes que acuden al Hospital Teófilo Dávila en el primer semestre del 2010 - Quizhpe Chiliquinga, María C. (2011)
We perfomed a retrospective descriptive study of patients treated in the department of gynecology and obstetrics at Teofilo Davila hospital, with 85 pregnant teenagers that had abortion, which corespondo to early , middle and late adolescence